Study of the Influence of Clay Minerals on the Mechanical and Percolation Properties of Weakly Cemented Rocks. (20th June 2022) - Guo, Shiru; Pu, Hai; Yang, Mengsen; Liu, Ding; Sha, Ziheng; Xu, Junce
Abstract : The weakly cemented rock layer is easily damaged under the combined effect of seepage and mining disturbance and creates massive engineering disasters. This paper uses the self-designed weakly cemented remodeling mechanism to prepare weakly cemented rock samples with clay minerals accounting for 20%, 30%, 40%, 50%, and 60% of the total. The MTS816 system, in conjunction with an acoustic emission system and a high-speed camera, completed mechanical and seepage tests on the sample. The results show that when the quantity of clay minerals increases, the uniaxial compressive strength, elastic modulus, and rapid crack propagation stress of the weakly cemented rock samples decrease. Initial stress of crack development increases and then decreases, as well as the sample's failure mode changes from shear to tensile. The sample's permeability increases with increasing osmotic and axial pressure differential but decreases with increasing confining pressure under the same amount of clay minerals. The sensitivity of permeability to changes in osmotic pressure differential, axial pressure, and confining pressure increases as the amount of clay minerals increases. The mechanical and seepage characteristics can show significant changes in clay minerals in 20% to 30%.